THE USE OF SONGS TO IMPROVE STUDENTS’ LISTENING COMPREHENSION ABILITY - Ni Luh Gede Windy Lestary; Si Luh Nyoman Seriadi (Yavana Bhasha : Journal of English Language Education, 2019)
The aim of this journal is to find out the utilization of songs as the techniqueof teaching listening. Listening is part of four Basic English language skills. It seemslike the other skills such as writing, reading, and speaking. These basic skills aredivided into receptive skill-listening and reading- and productive skill, speakingand writing. Music and songs are crucial parts of growing and learning. There aremany advantages to using songs in the classroom. There are positive and negativeviews on the utilization of songs in foreign language teaching. Using songs in thelearning process especially in the listening lesson it makes the students can improvetheir listening skill as one of their meaningful strategies to overcome their problemin listening skill. English song can make the students become active in the class,they are interesting, and so they can do a listening task well. However, utilizingsongs in the listening process has the challenges, such as; pop songs are notscientific, and inefficient sound systems in schools may cause problems whilelistening to songs, etc.